2019
DOI: 10.1021/acs.jpcc.9b07662
|View full text |Cite
|
Sign up to set email alerts
|

Probing a Ruthenium Coordination Complex at the Ionic Liquid–Vacuum Interface with Reactive-Atom Scattering, X-ray Photoelectron Spectroscopy, and Time-of-Flight Secondary Ion Mass Spectrometry

Abstract: The speciation, conformation, and reactivity of transition metal complexes at the gas−liquid interface are poorly understood, yet the potential is high for observing chemistry unique to this anisotropic interface and leveraging interfacial structure to control the state and environment of the complex. If transition metal complexes can be designed to populate a liquid−vacuum interface preferentially, then it may be possible to explore catalytic behavior by delivering reactants to the interface with a molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…4 Previous studies have indicated that the nature of the ligands influence the concentration profile of the catalyst complex in solution, which may range from homogeneous distribution to surface enrichment or depletion at the interface. [5][6][7][8][9][10][11][12][13] If the catalyst tends to accumulate near the gas/IL interface, the total process is expected to be more efficient. Therefore, it is crucial to determine the factors influencing the surface enrichment of catalysts in ILs, a matter that has not been fully elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…4 Previous studies have indicated that the nature of the ligands influence the concentration profile of the catalyst complex in solution, which may range from homogeneous distribution to surface enrichment or depletion at the interface. [5][6][7][8][9][10][11][12][13] If the catalyst tends to accumulate near the gas/IL interface, the total process is expected to be more efficient. Therefore, it is crucial to determine the factors influencing the surface enrichment of catalysts in ILs, a matter that has not been fully elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed study by the groups of J. M. Slattery and T. K. Minton revealed enrichment of a Ru catalyst at the IL/vacuum interface in [C 2 C 1 Im][Tf 2 N] by reactive‐atom scattering (RAS), time‐of‐flight secondary ion mass spectrometry (TOF‐SIMS) and X‐ray photoelectron spectroscopy (XPS) [13] . The ligand system featured the non‐polar phosphine ligand P(C 8 H 17 ) 3 , which is proposed to induce preferential population of the complex at the outer surface due to the aliphatic octyl chain [13] . The importance of the ligands’ nature on the surface behavior of organometallic complexes was also investigated by our group over the past years [14] .…”
Section: Introductionmentioning
confidence: 99%
“…[13] The ligand system featured the non-polar phosphine ligand P(C 8 H 17 ) 3 , which is proposed to induce preferential population of the complex at the outer surface due to the aliphatic octyl chain. [13] The importance of the ligands' nature on the surface behavior of organometallic complexes was also investigated by our group over the past years. [14] Recently, we demonstrated that the concentration profile of Pt complexes can be deliberately altered by manipulating the ligand system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of a study aimed initially at understanding the properties of imidazolium ILs at the gas-liquid interface using reactive atom scattering, 20,[26][27][28][29][30][31][32][33][34][35][36] a series of mixtures was prepared with the composition [C 12 mim] x [C 2 mim] 1Àx [Tf 2 N] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%